Delayed appearance of 3‐methylglutaconic aciduria in neonates with early onset metabolic cardiomyopathies: A potential pitfall for the diagnosis. Issue 1 (15th November 2019) - Baban, Anwar; Adorisio, Rachele; Corica, Bernadette; Rizzo, Cristiano; Calì, Federica; Semeraro, Michela; Taurisano, Roberta; Magliozzi, Monia; Carrozzo, Rosalba; Parisi, Francesco; Dallapiccola, Bruno; Vaz, Frédéric M.; et al.
Abstract: Infantile onset cardiomyopathies are highly heterogeneous with several phenocopies compared with adult cardiomyopathies. Multidisciplinary management is essential in determining the underlying etiology in children's cardiomyopathy. Elevated urinary excretion of 3‐methylglutaconic acid (3‐MGA) is a useful tool in identifying the etiology in some metabolic cardiomyopathy. Here, we report the delayed appearance of 3‐MGA‐uria, between 6 and 18 months in three patients (out of 100 childhood onset cardiomyopathy) with neonatal onset cardiomyopathy, secondary to TMEM70 mutations and TAZ mutations (Barth syndrome), in whom extensive metabolic investigations, performed in the first weeks of life, did not display 3‐MGA‐uria. Serial retrospective evaluations showed full characteristic features of TMEM70 and TAZ mutations (Barth syndrome) in these three patients, including a clearly abnormal monolysocardiolipin/cardiolipin ratio in the two Barth syndrome patients. Serially repeated metabolic investigations finally discovered the 3‐MGA‐uria biomarker in all three patients between the age of 6 and 18 months. Our observation provides novel insights into the temporal appearance of 3‐MGA‐uria in TMEM70 and TAZ mutations (Barth syndrome) and focus the importance of multidisciplinary management and careful evaluation of family history and red flag signs for phenocopies in infantile onset cardiomyopathies.